Evaluating risk factors for biceps tendon injuries in softball players: A systematic review - Stamm, M. A.; Brahmbhatt, P. S.; Brown, S. M.; Miskimin, L. C.; Mulcahey, M. K. (Clinical Journal of Sport Medicine, 2023)
Objective: Softball players commonly suffer overuse injuries due to the demands of repetitive throwing. The biceps tendon plays an important role in stabilizing the shoulder during the windmill pitch. The purpose of this study was to evaluate the measures used to identify and study biceps tendon pathology in softball players.